2020
DOI: 10.3221/igf-esis.53.36
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Stacking Sequences Effects in Composite Mechanical Joints under Impact Loadings

Abstract: The paper deals with composite structures in the field of advanced and modern structures in engineering design and according to high specification of composite materials such as high strength to weight ratio use in various industries such as aerospace, marine. One of the most important fields that Researchers have paid less attention to that is to investigate the effect of stacking sequence on the strength of mechanical joints under impact loading. In view of changing the mechanical properties of composite mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The findings of this study showed that the design process was reliable and the safety of CRSCs is considered; however, the probability failure for mid-rise CRSCs was more than low-rise prototypes [21]. Apart from the above mentioned studies, very little attention has been paid to experimental researches for understanding the structural behavior of buildings against vehicles collision due to its setup and an expensive procedure [22,23]. Therefore, this is a major reason for developing the analytical models based on probabilistic approaches to perceive the performance of buildings under vehicle impact.…”
Section: Introductionmentioning
confidence: 90%
“…The findings of this study showed that the design process was reliable and the safety of CRSCs is considered; however, the probability failure for mid-rise CRSCs was more than low-rise prototypes [21]. Apart from the above mentioned studies, very little attention has been paid to experimental researches for understanding the structural behavior of buildings against vehicles collision due to its setup and an expensive procedure [22,23]. Therefore, this is a major reason for developing the analytical models based on probabilistic approaches to perceive the performance of buildings under vehicle impact.…”
Section: Introductionmentioning
confidence: 90%
“…The critical values of geometric parameters for using metal inserts in the holes was 4. Fathi et al 13 investigated the strength of pin joints with different orientations of glass-fiber layers subjected to low-velocity tensile impact. The study concluded that the layers of 45° fibers in the model were essential.…”
Section: Introductionmentioning
confidence: 99%